Hubungan Mutu Pelayanan dengan Kepuasan Pasien Rawat Jalan di Rumah Sakit Paru Manguharjo Madiun Tahun 2023 - Asmirati Yakob; Lina Alfiyani; Yuli Kusumawati; Avi Arya Buana Jaya Putra; Kristofara Karolina Kewa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Health services which is execllent is able to refer to prime levels that are implemented on basis of service and code of ethics. Those will create a satisfaction for each patient. To measure the quality of service, there are several references, including; tangibles, reliability, empathy, assurance, and responsiveness. This study investigated the correlation between service quality and outpatient satisfaction at Manguharjo Lung Hospital (RS Paru Mangunharjo), Madiun, East Java. All the specimens in this research were outpatients where purposive sampling is used to determine the research sample. Data Accomodation technique is carried out by questionnaire. The output of the research, from 80 respondents asked about the relation between service quality and outpatient satisfaction at Manguharjo Lung Hospital, it can be concluded that there are dealings among Reliability, Assurance Tangibles, Empathy, and Responsiveness. The outcome of this research is ecpected to contribute theoritically such escalating quality development especially in public institutions, namely hospitals. Practically, It can be a consideration in arranging the policies that relate about hospital service particularly for outpatient service cases.